Olé : Esther Tielemans, Kim Engelen, Saskia De Ruiter, Tessa Joosse, Stephanie De Coo, G.C. Van Der Velden, Sopo Bazgadze, Eva Bonneur, Marlou Claassens, Jon Sund, Femke De Roos, Pieter Dobbelsteen, Harm Kuiper, Alexandra Crouwers, Esther Van Westen. - 's-Hertogenbosch; Teeken, Toon ('s-Hertogenbosch : Akademie voor Kunst en Vormgeving Hogeschool, 1998)
Tielemans, Esther ; Engelen, Kim ; De Ruiter, Saskia ; Joosse, Tessa ; De Coo, Stephanie ; Van Der Velden, G C ; Bazgadze, Sopo ; Bonneur, Eva ; Claassens ; Sund, Jon ; De Roos, Femke ; Dobbelsteen, Pieter ; Kuiper, Harm ; Crouwers, Alexandra ; Van Wester, Esther
's-Hertogenbosch
kunstcatalogus